Large scale biomonitoring of glyphosate and AMPA by analysis of human and animal feces and comparison with urine - Dias, Jonatan; Yen, Ling; Alcon, Francisco; Contreras, Josefa; Abrantes, Nelson; Campos, Isabel; Baldi, Isabelle; Bureau, Mathilde; Christ, Florian; Mandrioli, Daniele; Sgargi, Daria; Pasković, Igor; et al. (Elsevier, 2026)
Internal exposure of the world’s most used herbicide glyphosate and its environmental metabolite AMPA is commonly assessed by analysis of urine, while excretion is mostly through feces. In this study, we explore the feasibility and effectiveness of feces as an alternative matrix for urine for biomonitoring of these two compounds. A method for the determination of polar pesticides was validated and applied for analysis of 716 human and 249 animal feces samples. The samples were collected in 2021, at study sites in ten European countries and one in Argentina. Detection frequencies (DF) and median concentrations (MC) observed in sub-populations (conventional farmers, organic farmers, neighbors (rural), consumers (not involved in agricultural activities) were compared. Glyphosate was rather common in human feces in 71 % of the samples from the European sites and in 100 % of Argentinean samples. Detection in feces was more frequent than in the corresponding urine samples (35 % for Europe, 86 % for Argentina). MC in feces were 17.6 µg/kg (Europe) and 153 µg/kg (Argentina). Variation in DF and MC between study sites was larger than between pooled sub-populations of all study sites. In farm animals, glyphosate was found in the majority of the feces samples. AMPA was found less frequently, depending on the species and farming system. High concentrations of glyphosate and AMPA in bat feces showed that exposure also occurs at higher trophic levels in ecosystems near the investigated sites. In conclusion, analysis of feces reveals widespread exposure of both humans and animals to glyphosate, wider than so far reported based on urine as matrix.